Green marketing orientation: Evolution, conceptualization and potential benefits - Neringa Vilkaite-Vaitone; Ilona Skackauskiene (Open Economics, 2019)
Global economic fluctuation, post-Brexit challenges, changes in the landscape of corporate social responsibility are pushing managers to build sustainability into the performance of marketing mix. Traditional marketing is no longer able to address all the issues in modern markets. This led to green marketing, a new marketing philosophy. The paper provides researchers and marketing managers with a comprehensive view of the concept of green marketing, its causes, contents, and outcomes. Authors suggest a structured and outcome-based viewpoint to the construct of green marketing. Theoretical presumptions confirm structuration of green marketing initiatives to strategic, tactical, and operational levels. It was found out that cohesive marketing activities in these levels have the crucial impact of green marketing in organizational, environmental, and social contexts. Strategic, tactical, and operational activities in the field of green marketing may lead to business development, improvement of the natural ecosystem, and increased quality of life. The findings of the research present opportunities for researchers and managers to apply green marketing orientation.
Keywords: 330; ecological marketing; environmental marketing; environmentally friendly products; strategic green marketing; sustainable marketing